45 EPIDERMAL GROWTH FACTOR RECEPTOR SUBSTRATE 8 IS OVEREXPRESSED IN GONADOTROPINOMAS. (1st January 2006) - Ronnekleiv-Kelly, S.; Ariola-Tirella, R.; Xu, M.; Lillehei, K. O.; DeMasters, B. K.; Cary, L.; Wierman, M. E.
Abstract : Pituitary tumors are the most common intracranial neoplasm. Of the various types of tumors derived from the pituitary cell types (somatotrophs, lactotrophs, thyrotrophs, corticotrophs, or gonadotrophs), the gonadotropinomas commonly present as macroadenomas (tumors > 1 cm). Gonadotropinomas are FSHβ, LHβ and/or α-secreting tumors that account for approximately one-third of pituitary tumors and can result in hypogonadism, compress cranial nerves, and cause visual symptoms. Little is known about the pathophysiology of these tumors. We used DNA microarray technology (Affymetrix GeneChip Operating System with Human Genome U133 Plus 2.0 Array) to compare expression profiles from 10 gonadotropinomas to 9 normal pituitary samples (obtained at autopsy). A candidate gene list was prepared detecting genes that were 2-fold up or down in tumors compared to normal by pairwise analysis in at least 81/90 comparisons. One of the genes identified that was up-regulated in gonadotropinomas was Eps8, an epidermal growth factor receptor substrate. Eps8 has been previously shown to amplify growth factor signaling via interacting with epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR), vascular endothelial growth factor receptor (VEGFR) and insulin growth factor receptor (IGFR) signaling. In the microarray, Eps8 was up-regulated 5.53-fold in gonadotropinomas (90/90 comparisons) compared to normal pituitary (11, 460 ± 4, 730 vs 2, 072 ± 974). Eps8 has been shown to use the Sos-1/Rac pathway to reorganize the actin cytoskeleton and has been implicated in cell migration. We investigated a potential role of Eps8 in pituitary tumorigenesis using a modified Boyden chamber migration assay. α-T3 immortalized mouse pituitary gonadotrope cells stably overexpressing Eps8 (3.56-fold) were compared to vector transfected cells. In 10% serum (containing abundant growth factors), Eps8 overexpressing pituitary cells migrated more robustly than controls (4.1-fold), whereas only a 2.2-fold increase in migration was observed in low 0.2% serum. Together these data are consistent with a role of Eps8 in enhancing the migratory phenotype of gonadotropes in the presence of growth factors. Further studies are ongoing to examine the role of Eps8 as a protein involved in pituitary tumorigenesis.